Morphologic changes in hepatitis virus-related liver cirrhosis: Relationship to hemodynamics of portal vein on dynamic contrast-enhanced CT. Issue 2 (May 2021) - Yamamoto, A.; Ito, K.; Yasokawa, K.; Kanki, A.; Tanimoto, D.; Hayashida, M.; Tamada, T.
Abstract: Introduction: The morphologic changes in the compensated stage of liver cirrhosis (cLC) are not diffuse atrophic changes. With cLC lobar or segmental changes combined with atrophy of the right lobe and medial segment together with hypertrophy of the caudate lobe and lateral segment are commonly seen. The purpose of this study was to evaluate the morphologic changes in hepatitis virus-related liver cirrhosis in relationship to haemodynamics of the portal vein on dynamic contrast-enhanced computed tomography (DCE-CT) Methods: This study included 72 patients, 46 with hepatitis virus-related cirrhosis and 26 with a normally functioning liver, who underwent DCE-CT. In cirrhosis patients, the morphologic change index (MCI) of the liver was calculated and categorised into two groups, high-MCI (MCI ≥ 0.4) ( n  = 21) and low-MCI (MCI < 0.4) ( n  = 25). Cross-sectional areas of the main, right and left portal veins and the intra-portal distribution from splenic venous flow were evaluated for their relationships with the MCI and compared among three groups (normal-control, low MCI and high MCI). Results: There was a significant difference in the cross-sectional area of the left portal vein between the high-MCI group and the low-MCI group ( p  = 0.013) and the control group ( p  = 0.008). A significant correlation was identified between the cross-sectional area of the left portal vein and the MCI (r = 0.508, p  < 0.001). Conclusion: Cross-sectional area of the left portal vein may be a factor related to morphologic changes in hepatitis virus-related liver cirrhosis and could be a possible index of the left portal venous flow volume. Implications for practice: This study may be useful for predicting the degree of hepatic morphologic changes and the condition of cirrhosis in association with regional hepatic morphologic changes. Highlights: Left portal vein may be related to morphologic changes in cirrhosis. Intraportal flow distribution patterns didn't affect morphologic changes in cirrhosis. Left portal vein may be useful for predicting the degree of cirrhosis. Morphologic changes in hepatitis virus-related liver cirrhosis.